Tumor heterogeneity and carcinoma in resected specimens of gastric low-grade dysplasia: A retrospective single center study. - Ga-Yeong Shin; Jun Young Park; Sung Hak Lee; Yu Kyung Cho; Myung-Gyu Choi; Jae Myung Park (PLoS ONE, 2023)
Lesions diagnosed as gastric low-grade dysplasia (LGD) may be pathologically upgraded to early gastric cancer (EGC) or high-grade dysplasia (HGD) after endoscopic resection (ER). In this study, we investigated the risk factors for pathological upgrades after ER and assessed the reason for these upgrades by retrospectively analyzing ER data between January 1999 and December 2019. We enrolled patients with LGD confirmed by forceps biopsy; the patients were classified into pathologically concordant (LGD) and upgraded (HGD and EGC) groups according to the pathology of their resected specimen. To determine the risk factors for upgrade, we compared the endoscopic findings of the concordant and upgraded groups via 1:1 matched case-control design. To find the reasons for discordance, all upgraded cases were pathologically re-evaluated. Among 1,643 cases of LGD, pathological upgrades were observed in 423 (25.7%) resected specimens and EGC was found in 111 (6.7%) lesions. After matching the upgraded and concordant cases, lesion sizes exceeding 1.5 cm (odds ratio (OR): 1.8; 95% CI: 1.1-3.0), mucosal nodularity (OR: 10.8; 95% CI: 5.6-21.0), heterogeneous color (OR: 3.0; 95% CI: 1.7-5.3), presence of erosion (OR: 2.7; 95% CI: 1.8-5.3), and open-type gastric atrophy (OR: 2.9; 95% CI: 1.7-4.9) were noted to be significantly associated with upgraded pathology to EGC. Among the EGC cases, 99 (89.2%) were found to have pre-existing dysplasia. In conclusion, endoscopic evaluations should be performed because of possible pathological upgrades and co-existence of carcinomas in LGDs, especially when they exhibit surface nodularity, erosion, heterogeneous color, and large size.